Pure tone audiometry and cerebral pathology in healthy older adults. Issue 6 (27th May 2022) - Parker, Thomas; Keshavan, Ashvini; Buchannan, Sarah; Keuss, Sarah; Bamiou, Doris-Eva; Warren, Jason; Fox, Nick; Richards, Marcus; Schott, Jonathan
Abstract : Background: Hearing impairment may be a modifiable risk factor for dementia. However, it is unclear how hearing associates with pathologies relevant to dementia in preclinical populations. Methods: Data from 368 cognitively healthy individuals born during 1 week in 1946 (age range 69.2–71.9 years), who underwent structural MRI, 18F-florbetapir positron emission tomography, pure tone audiom- etry and cognitive testing as part of a neuroscience substudy the MRC National Survey of Health and Development were analysed. The aim of the analysis was to investigate whether pure tone audiometry performance predicted a range of cognitive and imaging outcomes relevant to dementia in older adults. Results: There was some evidence that poorer pure tone audiometry performance was associated with lower primary auditory cortex thickness, but no evidence that it predicted in vivo β-amyloid deposition, white matter hyperintensity volume, hippocampal volume or Alzheimer's disease-pattern cortical thickness. A negative association between pure tone audiometry and mini-mental state examination score was observed, but this was no longer evident after excluding a test item assessing repetition of a single phrase. Conclusion: Pure tone audiometry performance did not predict concurrent β-amyloid deposition, small vessel disease or Alzheimer's disease-pattern neurodegeneration, and had limited impact on cognitive function, in healthy adults aged approximately 70 years. thomasparker@nhs.net